PO 100 - ANESTHETIC CONCERNS IN A PATIENT WITH CONGENITAL MYASTHENIA GRAVIS AND SEVERE SCOLIOSIS - Ribas, Rita; Lakhani, Ria; Pereira, Susana; Carvalho, Ana Paula (Journal of the Portuguese Society of Anesthesiology, 2023)
x